Ceritinib (LDK378) prevents bone loss via suppressing Akt and NF-κB-induced osteoclast formation - He, Wenxin; Cao, Xiankun; Kong, Keyu; Rong, Kewei; Han, Shuai; Qin, An (Frontiers in Endocrinology, 2022)
Background Ceritinib is used for the treatment of patients with anaplastic lymphoma kinase (ALK)-rearranged non-small cell lung cancer (NSCLC), who are at the risk of developing bone metastasis. During bone metastasis, tumor cells release factors that induce osteoclast formation, resulting in osteolysis. However, the effect of ceritinib on osteoclast formation remains unclear. Methods Osteoclastogenesis was induced to assess the effect of ceritinib on osteoclast formation and osteoclast-specific gene expression. Western blotting was used to examine the molecular mechanisms underlying the effect of ceritinib on osteoclast differentiation. An in vivo ovariectomized mouse model was established to validate the effect of ceritinib in suppressing osteoclast formation and preventing bone loss. Results The differentiation of osteoclasts and the expression of osteoclast-specific genes were inhibited upon ceritinib stimulation. Ceritinib suppressed Akt and p65 phosphorylation during the receptor activator of nuclear factor kappa-B ligand (RANKL)-induced osteoclastogenesis. The administration of ceritinib to ovariectomized mice ameliorated trabecular bone loss by inhibiting osteoclast formation. Conclusions Ceritinib is beneficial in preventing bone loss by suppressing osteoclastic Akt and nuclear factor κB (NF-κB) signaling.